Primary amenorrhea: a clinical review - Samal, Rupal; Habeebullah, Syed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Primary amenorrhoea is a symptom with an extensive list of underlying causes, the majority of which are rare. According to the definition it should present in adolescence, although some conditions are diagnosed in childhood may present with failure of menstruation. Many causes of secondary amenorrhoea can also present with primary amenorrhoea if they arise very early in life. A systematic, compartment based approach will cover the commoner causes of primary amenorrhoea and recommend a pragmatic but cost-effective approach to achieve correct diagnosis. Treatment must be directed at the specific cause but has often wider implications for life long wellbeing like weight management, hormone replacement, sexual health and fertility.